Intersubjective strategies in deontic modality: evidential functions of Spanish deber ‘must’ - Thegel, Miriam (Kalbotyra, 2017)
The principal aim of this study is to examine the Spanish modal verb deber ‘must’ in its deontic readings, relating it to the notions of evidentiality and intersubjectivity. Deber has often been compared to the modal verb tener que ‘have to’ and described in rather vague terms, for example as an expression of weak, internal obligation, but this paper proposes that it is better understood as an intersubjective verb. Both quantitative and qualitative analyses have been carried out, with a special focus on the in-depth qualitative study. It will be shown that deontic deber can convey evidential meanings when used in the conditional form. First, it can refer to a norm shared between the speaker and the hearer, and, second, it can convey an inferential process, a conclusion presented by the speaker, which is based on shared information, available to a larger group (or all) of the interlocutors. Evidentiality is regarded here as an intersubjective strategy, used when the speaker wants to reach consensus, arguing for the most reasonable, morally defensible way to act. Thus, this study also offers a new perspective of evidentiality, looking at this notion in interaction with deontic modality instead of epistemic modality, which is usually the case.
Keywords: deontic modality; evidentiality; Spanish modal verbs; conditional tense; intersubjectivity